Restoring silvopastures with oak saplings: effects of mulch and diameter class on survival, growth, and annual leaf-nutrient patterns - Jiménez, M. N.; Pinto, J. R.; Ripoll, M. A.; Sanchez-Miranda, A.; Navarro, F. B. (Agroforestry Systems, 2014)
In Southwestern Spain, multifunctional silvopastoral systems consisting of pastureland and open oak woodlands are known as Dehesas. These, and other similar systems of the Mediterranean basin, are currently threatened by increasing intensive land use. As a consequence, oak regeneration is declining and is in need of adequate management and active restoration. Traditional restoration practices outplant one-year-old, nursery-produced oak seedlings grown in 250–350 cm3 containers, but establishment and growth results are typically poor. This work examines holm oak (Quercus ilex L. subsp. ballota (Desf.) Samp.) grown in a non-conventional container size (24 l) and age (6–7 years) with three mulch treatments (control, stone, and straw). In an open Dehesa of SE Spain, 106 oak saplings were planted in March 2010, and survival, diameter at breast height (DBH), and leaf-nutrient concentrations were analyzed. Forty months after planting, all treatments showed high survival (81 %) but only straw-mulched saplings differed significantly (94 %) from control (74 %). DBH increased over time but showed no significant differences among mulch treatments. Saplings with high initial DBH showed the greatest growth and change in DBH at the end of the study period. Leaf- nutrient concentrations changed significantly in the year following outplanting. Bi-monthly foliar nutrient concentration data show decreases in P, K, Zn, and B and sharp increases in Ca and Fe. In this work, we provide some evidence concerning the viability of non-conventional oak size for restoring, regenerating, or building up new agroforestry or silvopastoral systems. A combination of saplings with more than 10 mm of DBH and straw mulch is recommended.
Keywords: 10; 1007; ballota á saplings á; contains supple-; DBH; Dehesa; dehesa á mulch á; doi; electronic supplementary material the; Mulch; online version of; quercus ilex subsp; quercus ilex subsp. ballota; s10457-014-9737-y; Saplings; semi-arid; semi-arid á dbh á; Spain; this article

Is tree shelter protection an effective complement to weed competition management in improving the morpho-physiological response of holm oak planted seedlings? - Ceacero, Carlos J; Navarro-cerrillo, Rafael M; Díaz-Hernández, José Luis (iForest - Biogeosciences and Forestry, 2014)
Weed control is a key aspect that influences seedling response in newly-established plantations. Tree shelter protection may be an effective complement to weed control with a positive effect on the overall response of seedlings. Our study focused on assessing the morpho-physiological response of Holm oak (Quercus ilex L. ballota [Desf.] Samp.) plantations to weed control and individual protection as a combined cultural technique on a cropland site in southern Spain. The weed control treatments (cultivation, herbicide and mulch) were also applied in combination with tree shelters. Morpho-physiological variables including survival, aerial and root morphology, water potential, gas exchange and chlorophyll fluorescence were monitored over a 2-year period. Results showed that weed competition management treatments improved the seedling survival rate compared to the control treatment. Moreover, shelter was associated with a greater height growth. At early stages of establishment, and particularly under combined treatments, all plants invested more resources in their aerial parts than in their root system. Seedlings did not regulate water loss as a result of water stress, contrary to what would be expected in Mediterranean areas. Under all treatments, especially those combined with tree shelters, seedlings took up to 2 years to achieve morpho-physiological adaptation (i.e. height and diameter growths, water stress behavior) to site conditions. In addition, tree shelters promoted an increase in net photosynthesis compared to non-shelter treatments during the winter period. The tree shelters also limited the emergence of photo-inhibition phenomena in seedlings so that plants under combined treatments showed greater photo-chemical efficiency. Thus, this study supports the effectiveness of tree shelter protection as a complement to weed control treatments. More specifically, it suggests that combining individual protection (shelter) and weed control around seedlings is an interesting technique for reforestation of forest ecosystems in Mediterranean areas.
Keywords: Mulch; Oxyfluorfen; photoinhibition; photosynthesis; Tillage; tree shelter

Weed control modifies Tuber melanosporum mycelial expansion in young oak plantations - Olivera, Antoni; Antonio Bonet, Jose; Palacio, Lorena; Liu, Bing; Colinas, Carlos (ANNALS OF FOREST SCIENCE, 2014)
Black truffle (Tuber melanosporum) cultivation is a promising agro-forestry alternative for Mediterranean rural areas, but adequate weed control at seedling establishment still remains a challenge in black truffle plantations. The aim of this study is to evaluate the effects of several weed control strategies on early development of Quercus ilex seedlings and the symbiotic T. melanosporum. In a young black truffle-inoculated holm oak plantation, we assessed for 3 years the effects of two types of mechanical weed control and five mulches in a young Q. ilex plantation inoculated with T. melanosporum. Herbaceous cover, seedling growth and abundance of T. melanosporum mycelium, based on PCR analysis of soil DNA extracts using T. melanosporum-specific primers, were estimated to determine the effectiveness of these treatments in controlling weeds and supporting the growth of both the host tree and the target fungus. The amount of T. melanosporum mycelium in the soil 30 cm around the seedlings was larger under double-layer white mulch than in the rest of treatments tested. Under the white colour mulches, which had the largest light reflection, we registered the cooler soil temperature, and the best weed control was observed on the single- and double-layer black truffles and double-layer white mulch. The effects of double-layer white mulch on herbaceous cover, soil temperature, reflected light, and the expansion of T. melanosporum bring us closer to being able to substitute traditional tilling of truffle orchards for the less expensive mulching treatments.
Keywords: Mulch; Quercus ilex; Soil mycelium; Tubermelanosporum; Weed control